Genetic differentiation between close eastern Mediterranean Dicentrarchus labrax (L.) populations - Castilho, Rita (2014)
Differentiation at nine microsatellite loci revealed that a Levantine Basin sea bass Dicentrarchus labrax population probably represents a further subdivision of this species in the eastern Mediterranean.